Association Between Dietary Intake of One-Carbon Metabolism-Related Nutrients and Fluorosis in Guizhou, China - Chen, Ting; Tao, Na; Yang, Sheng; Cao, Dafang; Zhao, Xun; Wang, Donghong; Liu, Jun (Frontiers in Nutrition, 2021)
Abstract Objective. The main aim was to investigate the associations between dietary one-carbon metabolism-related nutrients (betaine, choline, methionine, folate, vitamin B6 and vitamin B12) and fluorosis among a Chinese population in an area known for coal-burning fluorosis. Methods. A cross-sectional study was conducted, with 653 fluorosis patients and 241 non-fluorosis participants. Dietary intake was acquired using a validated semi-quantitative 75-item food frequency questionnaire. Risk associations were assessed by unconditional logistical regression. Results. We observed a significant inverse association between dietary betaine, total choline, methionine, folate, vitamin B6 and choline species and fluorosis. The adjusted OR (95% CI) in the highest quartile of consumption compared with the lowest were 0.59 (0.37-0.94) (P-trend = 0.009) for betaine intake, 0.45 (0.28-0.73) (P-trend = 0.002) for total choline intake, 0.46 (0.28-0.73) (P-trend < 0.001) for methionine intake, 0.39 (0.24-0.64) (P-trend < 0.001) for folate intake, 0.39 (0.24-0.63) (P-trend < 0.001) for vitamin B6 intake and 0.46 (0.29-0.75) (P-trend = 0.002) for total choline plus betaine intake. Dietary intakes of choline-containing compounds, phosphatidylcholine, free choline, glycerophosphocholine and phosphocholine were also inversely associated with lower fluorosis (all P-trend < 0.05). No significant associations were observed between dietary vitamin B12 or sphingomyelin and fluorosis. Conclusion. The present study suggested that higher dietary intakes of specific one-carbon metabolism-related nutrients, such as betaine, choline, methionine, folate and vitamin B6, are associated with lower fluorosis prevalence.